Over the counter low-dose cannabidiol: A viewpoint from the ACRE Capacity Building Group. (June 2022) - Hallinan, Christine Mary; Eden, Edward; Graham, Myfanwy; Greenwood, Lisa-Marie; Mills, Jessica; Popat, Amirali; Truong, Linda; Bonomo, Yvonne
Amidst growing global acceptance of medicinal cannabinoids as a potential therapeutic interest in cannabidiol (CBD) is increasing. In Australia in 2020, a government inquiry examined the barriers that the public are experiencing in accessing medicinal cannabis. A number of recommendations to improve access were made. In response to these recommendations, the Australian therapeutics regulatory authority down-scheduled CBD from Prescription Only (Schedule 4) to Pharmacist Only (Schedule 3). As a group of early to mid-career researchers of the Australian Centre for Cannabinoid Clinical and Research Excellence (ACRE), we propose some considerations in relation to over-the-counter availability of CBD and opportunities to improve knowledge about its potential therapeutic benefits alongside its increased uptake.